An appeal from Porto Rico Committee on Resolutions of the Republican National Convention at Chicago - Todd, Roberto H. (My University, 1920)
Convención que trata el tema sobre el esquema propuesto para la plataforma que incorpora Puerto Rico como un territorio.
Keywords: Republican National Convention; Puerto Rico--Politics and government.; Self-determination, National--Puerto Rico.; Convención Nacional Republicana; Puerto Rico--Política y gobierno.; Autodeterminación, Nacional--Puerto Rico.